ANALISA ORGANOLEPTIK POMADE BERBASIS PALM FATTY ACID DISTILLATE DAN GLISERIN - Siregar, Leonardi; Zakwan, Zakwan; Raja, Pada Mulia (Institut Teknologi Sawit Indonesia (ITSI), 2021)
Palm Fatty Acid Distillate (PFAD) is a by-product of the palm oil refining process which contains 80% of free fatty acids (ALB). Overall the palm oil manufacturing process will produce 73% olein, 21% stearin, 5-6% PFAD and 0.5% trench CPO. CPO can be used to produce solid palm oil (RBD stearin) and liquid palm oil. PFAD is a by-product of the Fractionation process at the Downstream Industry plant, which can add value to the industry if it is developed, for example, as a raw material for pomade. This study aimed to determine the quality of pomade hair oil based on PFAD and Glycerine using the organoleptic method. The stages of this research are; (1). Sampling (2). Deodorization (3). Pomade Making (4). Organoleptic analysis (5). Test data using LSR (BNT). The color BNT test analysis results with the notation of 0.01 and 0.04 seem to give a significant difference in the aroma analysis test P1M1 P2M2 with P3M3 P4M4 P5M5 it looks very significant and the results of the texture analysis test also show a very significant difference.